A pilot study of Livin gene and Yes-associated protein 1 expression in hepatocellular carcinoma patients - Eman AE. Badr; Ibrahim El Tantawy El Sayed; Mohamed FA. Assar; Sahar AM. Ali; Nehal S. Ibrahim (Heliyon, 2019)
Background: Livin gene and Yes-Associated Protein 1 (YAP1 (play a pivotal role in organ size control and tumorigenesis. Aim: In the present pilot study, we investigate the expression of Livin gene and YAP1 in hepatitis C virus (HCV) associated hepatocellular carcinoma (HCC) compared to other HCV patients and controls.Methods: the studied patients were divided into three groups 30 patients in each group in addition to 30 healthy subjects as a control group. Relative quantification of Livin gene and YAP-1 were assessed by quantitative Real Time RT-PCR (qPCR) in all studied patients and healthy controls. other laboratory investigations were done including complete blood count (CBC),international normalized ratio (INR) as well as liver function tests and tumor markers. Results: Significant overexpression of Livin gene and YAP-1 was detected in HCC group followed by Hepatitis C Virus (HCV) untreated group then HCV treated group. The relative quantitation (RQ) of both genes showed positive correlation to the carcinoembryonic antigen (CEA) level and a significant relation was found between higher level of Livin and YAP1 genes and tumor size. The overall survival rate was low in those patients with high levels of Livin and YAP 1 genes so they were considered as indicators of a bad prognosis. Conclusion: There is overexpression of Livin gene and YAP1 in hepatocellular carcinoma patients. They can be used as indicators of bad prognosis of the disease pathway together with low survival rate.